2020
DOI: 10.1007/s42991-020-00011-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of attractants to increase camera trap detections of North American mammals

Abstract: Camera traps are a cost-effective tool for large-scale and long-term population monitoring of mammals. Either bait or lure is often used to attract animals in front of a camera; however, the relative efficiency of these two attractants, or their combination, is not well understood. Our objective was to determine the optimal attractant setup for maximizing detection probabilities of mammals in the northeast USA. We conducted a camera trapping project in northern Maine, USA, from August to November 2018, and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 54 publications
(65 reference statements)
0
24
0
1
Order By: Relevance
“…Attractants such as baits (food reward) and lures (non-food reward) are often used in carnivore studies to increase encounter events (Schlexer 2008). However, responses to attractants can vary greatly among species, making choice of attractants an important aspect of study design in multi-species studies (Du Preez et al 2014, Ferreira-Rodríguez and Pombal 2019, Buyaskas et al 2020, Holinda et al 2020. Seasonal timing of the survey can influence inference regarding habitat use or activity patterns (Kays et al 2020) and affect encounter frequencies, particularly for species that hibernate or exhibit seasonal differences in density (e.g.…”
mentioning
confidence: 99%
“…Attractants such as baits (food reward) and lures (non-food reward) are often used in carnivore studies to increase encounter events (Schlexer 2008). However, responses to attractants can vary greatly among species, making choice of attractants an important aspect of study design in multi-species studies (Du Preez et al 2014, Ferreira-Rodríguez and Pombal 2019, Buyaskas et al 2020, Holinda et al 2020. Seasonal timing of the survey can influence inference regarding habitat use or activity patterns (Kays et al 2020) and affect encounter frequencies, particularly for species that hibernate or exhibit seasonal differences in density (e.g.…”
mentioning
confidence: 99%
“…The bait consisted of American beaver ( Castor canadensis ) carcasses, which were cut to standard size ( = 0.22 kg) and protected by a suet cage approximately 2 m in front of the camera at an average height of 30 cm above the ground. In a previous study we demonstrated that the simultaneous use of bait and lure increased the detection probability of carnivore species without impacting non-carnivore mammals 23 . Specifically, we found that for mustelid species and for the black bear, the combined use of a bait and lure drastically increase detection, as an example the probability of detecting a marten increased from 0.1 to 0.5.We deployed survey stations in the summer season for > 15 days, and during the following winter season for > 15 days.…”
Section: Methodsmentioning
confidence: 89%
“…Our previous work has shown that the use of bait and lure clearly maximizes detection of carnivores (mustelids in particular) without affecting detection of non-target species 23 . A more neutral approach (no bait or lure) would likely work too, however in our case detection probabilities would have been extremely low, leading to very high sampling efforts 23 . Further, we emphasize that our sampling unit was a transect with three cameras, which maximizes detections and reduces the variance in parameter estimates 1 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, attraction to bait can introduce heterogeneity due to behavioral variation among individual animals within [11] and between species [1,25] and temporal variation in detection probability as the bait degrades or is eaten. Nonetheless, these problems might be offset by increased detection probability and by keeping an animal in front of the camera long enough for a good picture, especially for single species studies where comparisons across the community are less important [4]. Placing camera traps along fine-scale habitat features (e.g.…”
Section: Discussionmentioning
confidence: 99%